Evaluation of atmospheric intensity turbulent by polarimetric radar - Авер’янова, Ю.А.; Аверьянов, A.А.; Яновський, Ф.Й. (Proceedings of National Aviation University, 2006)
The approach to retrieve information on turbulence intensity in liquid precipitation with polarimetric spectrum parameters is proposed. Turbulence is considered as random process. Drops are considered as factors that provide polarization spectrum appearance. Polarimetric spectrum of received signal depends on hydrometeor aerodynamics that is described with transient characteristic. The calculation results confirm the possibility to use the polarimetric spectrum parameters for turbulence characteristic.